Combined systemic immune-inflammatory index and prognostic nutritional index predict outcomes in advanced non-small cell lung cancer patients receiving platinum-doublet chemotherapy - Fan, Ruiyun; Chen, Ying; Xu, Guopeng; Pan, Wen; Lv, Yantian; Zhang, Zhongwei (Frontiers in Oncology, 2023)
Background: Systemic immune-inflammatory index (SII) and prognostic nutritional index (PNI) could evaluate the therapeutic efficacy and prognosis in different tumors. However, no studies investigated the SII-PNI score to predict outcomes in non-small cell lung cancer (NSCLC) patients treated with first-line chemotherapy. The aim of this study was to investigate the SII-PNI score in predicting outcomes in non-small cell lung cancer (NSCLC) patients treated with first-line chemotherapy. Materials and Methods: Our study retrospectively analyzed clinical data from 124 patients with advanced NSCLC receiving the first-line platinum-based chemotherapy. The SII and PNI were calculated based on peripheral blood cell counts and serum albumin, and the optimal cut-off values were determined using receiver operating characteristic (ROC). All patients were divided into three groups according to the SII-PNI score. The association between the SII-PNI score and the clinicopathological characteristics of the patients was examined. The Kaplan-Meier model and the Cox regression model were used to assess progression-free survival (PFS)and overall survival (OS). Results: There was no significant correlation between SII, PNI at baseline and prognosis in patients with advanced NSCLC (P>0.05). However, the SII and PNI after four cycles of chemotherapy were significantly correlated with PFS (all P < 0.001), as well as with OS (P < 0.001 and P = 0.002). The PFS of patients with SII-PNI scores of 0, 1, and 2 were 12.0, 7.0, and 5.0 months, and the OS of patients with SII-PNI scores of 0, 1, and 2 were 34.0, 17.0, and 10.5 months, respectively. There was statistical significance among the three groups (all P <0.001). Multivariate analyses showed that the chemotherapy response of progressive disease (PD) (HR:2.366, 95% CI: 1.111-5.040) and SII-PNI score of 2 (HR:4.847,95%CI: 2.667-08.807, P < 0.001) were independently associated with a shorter OS. Conclusion: The SII-PNI score after four cycles of chemotherapy is an effective prognostic biomarker for advanced NSCLC patients treated with first-line platinum-based chemotherapy. Patients with a higher SII-PNI score had a worse prognosis.